Progesterone and lutenising hormone profile of Saanen crossbred goats synchronised with CIDR and PMSG - Mohamad Salleh, Suraya; Panandam, Jothi Malar; Yaakub, Halimatun (Malaysian Society of Animal Production, 2014)
A better understanding of the hormonal profile of oestrus synchronised Saanen crossbreds would guide appropriate timing of Fixed Time Artificial Insemination (FTAI). This study was conducted to determine the progesterone hormone (P4) and luteinising hormone (LH) concentrations from the end of oestrus synchronisation treatment until the estimated time of ovulation. The LH peak would help in estimating the time of ovulation and appropriate time for FTAI. Twenty three Saanen crossbred does aged 2 to 4 y were allocated to three treatment groups: i) CIDR for 14 d and PMSG and PG at CIDR removal (CIDR14++; n=8); ii) CIDR for 9 d and PMSG and PG at CIDR removal (CIDR9++; n=8); iii) CIDR for 9 d and only PG at CIDR removal (CIDR9+; n=7) intramuscularly. Oestrus signs were recorded and blood samples were collected every 4 h beginning at 24 h post CIDR removal for 24 h. The serum samples were analyzed for P4 and LH concentration using ELISA kits. The CIDR9++ does had shorter (p<0.05) interval between CIDR removal and onset of oestrus than the other two treatment groups. All protocols showed declining P4 hormone concentration after 24 h of CIDR removal. The CIDR14++ does had highest mean LH concentration at peak (8.03±2.07 mIU/ml), followed by CIDR9+ does (7.32±1.07 mIU/ml); these values were higher (P<0.05) than the mean for the CIDR9++ does (4.94±0.80 mIU/ml). The LH peak occurred at 42.0±1.15, 41.0±1.91, and 43.0±1.00 h after CIDR removal for the CIDR14++, CIDR9++, and CIDR9+ treatments, respectively. The use of the intravaginal CIDR for oestrus synchronisation may be shortened in goats to 9 d while there was no significant difference in the time of occurrence of LH peak.